Seismic attribute analysis of the Mississipian limestone: Ness County, Kansas - Mourning, Rusty C. (Kansas State University, 2014)
Ness County has contributed 30 billion barrels to Kansas oil production since 1995, and has been an actively developing county in oil activity. The focus of this research project is to identify the reservoir qualities that make Mississippian-aged production favorable. Modern day logging techniques and seismic data allow specialists to seek out subtle heterogeneities to an oil producing formation once thought to be homogenous. Having success with horizontal drilling in other locations worldwide, large oil companies have acquired tens of thousands of acres with the intentions of drilling into the Mississippian, although some have recently backed out of the area. While some horizontal wells are producing today, complications with the compartmentalized, relatively thin Mississippian producing zones and short production longevities make horizontal drilling a high risk technique. Better understanding favorable reservoir qualities are essential for future production and development of oil fields in Ness County. This case study utilizes different variations of post and pre-stack 3D and 2D seismic data shot on about 3,200 acres spanning over 8 sections located in northwestern Ness County. The physical and chemical properties associated with the Mississippian formation in this area can be better analyzed with different methods for processing seismic data. Raw seismic signatures show little variation within the Mississippi Lime/Dolomite. Utilizing Seismic attributes derived from raw data may bring certain featured hydrocarbon bearing zones into view. Attributes such as curvature and coherency aid in interpreting physical features within the study area while spectral decomposition, amplitude, instantaneous frequency, and instantaneous Q hold detailed signatures dependent upon rock properties.
Keywords: Seismic Attribute Mississippian Lime Oil; Geology (0372); Geophysics (0373)